SISTEM E-LEARNING BERBASIS MODEL MOTIVASI KOMUNITAS (Jurnal TEKNODIK, 2018)
e-Learning system is a required solution in education at this globalization era. The existence of e-Learning with information tecnology support bring the transformation from conventional education process into digital form, both content and system perspective. However, recently e-Learning industry is experiencing of crisis, causing to failure and lack of e-Learning implementation in various sector in the world. Failure is especially caused by limited number of user and the lack of motivation to finish eLearning. This paper give solution by developing e-Learning system based on community motivation model which able to overcome the problems regarding to user motivation in the implementation of e-Learning system. Model is developed based on the theory of learning motivation and requirement capturing from the requirement engineering’s field. The indicators used to measure the model effectiveness are hit and visit statistics, traffic ranking, comparison with other similar e-Learning system, and the relation between concepts in model. Community motivation model have been implemented in web based public e-Learning systems (IlmuKomputer.Com), with the significant results appeared